Seed size, shape and persistence in soil: a test on Italian flora from Alps to Mediterranean coasts - Cerabolini, Bruno; Ceriani, Roberta M.; Caccianiga, Marco; Andreis, Rossella De; Raimondi, Barbara (Seed science research, 2003)
Seed size is a good predictor of seed persistence in soil for British, Argentinean, Iranian and – to some extent – New Zealand species. It has been suggested that seed shape should also be linked to the ease of burial and, thus, to seed persistence, even if some studies failed to show this. The relationship between seed size and shape and persistence in soil was analysed for 259 species of the Italian flora, belonging to a wide range of habitats, from alpine pasture to limestone prairies and meadows of the Prealps, and from woodlands to Mediterranean maquis and garigues. Seed size was related to persistence in soil in the same way as in most other floras examined. Furthermore, seed shape was highly related to persistence in soil among the species analysed, when considered both altogether and divided among the different habitats. Our results suggest that not only seed size, but also seed shape, are key factors in determining seed fate and seed persistence in soil.